MAGIC FOURANGLE OF MICROECONOMICS - N.I. KOTOV (Advanced Engineering Research, 2007)
Magic fourangle of microeconomics represents income - demand - substitution effect - supply. The article is devoted to an opening of interconnections betwen them. Practical application economic is entrepreneur's policy based on objective results of marketing.